Bisphenol A triggers axonal injury and myelin degeneration with concomitant neurobehavioral toxicity in C57BL/6J male mice. (1st December 2019) - Khan, Jasim; Salhotra, Shikha; Goswami, Poonam; Akhter, Juheb; Jahan, Shagufta; Gupta, Sakshi; Sharma, Shikha; Banerjee, Basu Dev; Parvez, Suhel; Gupta, Sarika; Raisuddin, Sheikh
Graphical abstract: Highlights: Bisphenol A causes axonal degeneration and behavioral alteration in mice. Long-term bisphenol A causes cerebral demyelination. Bisphenol A-induced oxidative stress is implicated in cerebral cortex injury. Pro-inflammatory environment may support neuroinflammatory disease onset. Abstract: Bisphenol A (BPA) is a ubiquitously distributed endocrine disrupting chemical (EDC). BPA exposure in humans has been a matter of concern due to its increased application in the products of day to day use. BPA has been reported to cause toxicity in almost all the vital organ systems even at a very low dose levels. It crosses the blood brain barrier and causes neurotoxicity. We studied the effect of BPA on the cerebral cortex of C57BL/6J mice and examined whether BPA exposure alters the expression of axonal and myelin structural proteins. Male mice were dosed orally to 40 μg and 400 μg BPA/kg body weight for 60 days. BPA exposure resulted in memory loss, muscle coordination deficits and allodynia. BPA exposure also caused degeneration of immature and mature oligodendrocytes as evaluated by decreased mRNA levels of 2′, 3′-cyclic nucleotide 3′ phosphodiesterase (CNPase), nestin, myelin basic protein (MBP) and myelin-associated glycoprotein-1 (MAG-1) genes revealing myelin related pathology. It was observed that subchronic BPA exposure caused neuroinflammation through deregulation of inflammatory cytokines mRNA and protein expression which further resulted into neurotoxicity through axonal as well as myelin degeneration in the brain. BPA also caused increased oxidative stress in the brain. Our study indicates long-term subchronic low dose exposure to BPA has the potential to cause axonal degeneration and demyelination in the oligodendrocytes and neurons which may have implications in neurological and neuropsychological disorders including multiple sclerosis (MS), neuromyelitis optica and others.